Assessment of knowledge, attitudes, practices, and self-efficacy toward evidence-based medicine among resident physicians: a cross-sectional study from Qatar - Mohammed Ahmed, Wafa; Aabdien, Mohamed; Mohamed, Abdelaziz; Bougmiza, Mohamed Iheb (Frontiers in Medicine, 2025)
IntroductionEvidence-based medicine (EBM) is essential for delivering high-quality healthcare. However, no studies have yet assessed the practice of evidence-based medicine among resident doctors in Qatar. This study aimed to examine the key factors influencing EBM practice, focusing on the physicians’ self-efficacy, self-reported knowledge, and their attitudes toward EBM.MethodologyAn analytical cross-sectional study design was used, using a total population sampling method. Data were gathered through a validated questionnaire to assess EBM practices among resident physicians at HMC. Descriptive statistics, bivariate analysis, and multivariate analysis were used to analyze the data.ResultsA total of 355 resident physicians participated in the survey. The average age of the participants was 28.3 years. The overall EBM practice score averaged 38, indicating a moderate level of practice according to the Bloom scale. Significant associations were found between EBM practice and physician age, gender, work experience, and prior EBM training. The majority of participants demonstrated moderate knowledge of EBM but had low attitudes toward its application. Additionally, the resident physicians exhibited low self-efficacy in applying EBM.ConclusionWhile the work environment in Qatar is highly supportive of EBM practice and the resident physicians possess strong academic qualifications, their overall practice of EBM remains moderate. This could be attributed to their relatively young age, limited experience, and unfavorable attitudes toward EBM, along with low self-efficacy. There is a need for targeted training workshops to improve EBM skills and attitudes among resident physicians, which could enhance their practice and, ultimately, improve patient outcomes in Qatar.